Development of Automated Exosome Isolation Method Using Epigallocatechin Gallate-Modified Magnetic Beads: Standardized Protocols for Diverse Biofluids - Heejong Shin; Eunju Jeong; Seunggwan Lee (Applied Sciences)
Exosomes are 30–150 nm extracellular vesicles that play crucial roles in intercellular communication and hold significant potential as biomarkers for non-invasive liquid biopsy. However, the current isolation methods have limitations including being time-consuming, producing low yields, and having high costs. This study presents a novel automated exosome isolation method using EGCG-modified magnetic beads (EGCG@T) optimized for diverse biofluids including plasma, serum, urine, and saliva. We systematically investigated the optimal EGCG:T-Fe3O4 ratio (0.1:1), binding time, elution parameters, and extraction buffer composition for each biofluid type. The developed protocol was successfully integrated into an automated workflow using the Nextractor® NX-Junior platform, combining exosome isolation and protein extraction into a single step. Western blot and ELISA analyses confirmed that the EGCG@T method yielded a significantly higher recovery of exosomal markers (CD9, CD63, CD81, TSG101, and ALIX) compared to conventional PEG precipitation, with the efficiency varying depending on the biofluid. Notably, CD63-positive exosomes were isolated with approximately two-fold higher efficiency from urine and 1.3-fold higher efficiency from saliva using the EGCG@T method. Our findings demonstrated that biofluid-specific optimization is essential for effective exosome isolation, as exosome subpopulations exhibited distinct physicochemical properties across different sample types. This automated, rapid, and efficient exosome isolation method provides a valuable platform for future clinical applications in non-invasive disease diagnosis and monitoring through liquid biopsy.